Studi Komparasi Pemikiran Elly Risman dan Konsep Perkawinan Islam dalam Pola Ketahanan Keluarga untuk Mencegah Kenakalan Remaja - Ely Muawanah (Rechtenstudent, 2020)
Family resilience consists of three things, namely physical, social, and psychological resilience. So, the application of this resilience pattern will lead to interactions between family members, so that happiness or family crises can emerge, such as juvenile delinquency. Thus the researcher is interested in comparing Elly Risman's thoughts and the concept of Islamic marriage. The focus of the studies examined in this article are: 1) What is the Pattern of Family Resilience to Prevent Juvenile Delinquency According to Elly Risman? 2) What is the pattern of family resilience to prevent juvenile delinquency according to the concept of an Islamic marriage? 3) How is the comparison between Elly Risman's thoughts and the concept of Islamic marriage in the pattern of family resilience to prevent juvenile delinquency? In this study, the authors took normative legal research. Based on the results and conclusions of research conducted by researchers, among others: 1) the concept of family resilience according to Elly Risman includes tips for being able to adapt and survive, factors of weakening family resilience, the impact of weakening family resilience, and efforts to maintain the family. 2) the concept of family resilience according to Islamic marriage includes the urgency of having a family, family goals, family wisdom, rights and obligations of family members, factors needed in family resilience as well as managing conflict and building family resilience. 3) The comparison of Elly Risman's thoughts and the concept of Islamic marriage in family resilience includes, Elly Risman's view on family resilience puts forward feelings that have an impact on psychology and family resilience that will have an impact on children's growth. Elly Risman also revealed the important role of parents in childcare. Whereas in the concept of Islamic marriage, it includes considering the purpose of having a family, prioritizing the rights and obligations of family members, and paying attention to equality.